The Study of Prevalence of Low Birth Weight Newborns in Hamadan's Meternity Hospitals During The First 9 Months of 1974 - H. Riazi; Dr. Gh. Sadri; M. Saeedi Jam (Tehran University of Medical Sciences, 2000)
The study of Prevalence of Low Birth Weight newborns in Hamadan's Maternity hospitals during the first 9 months in 1374.The purpose of this study was to ascertain the prevalence of low birth weight infants in Hamadan. For this reason the whole births during the first 9 months in year 1374 in Hamadan's maternity hospitals was studied and each of LEW infant was Considered as a "Case". Inspite of each LBW, two babies with normal weight was selected as Control group. The total number of records which were studied were 9145. Results showed that the prevalence of LBW is 10.8% . The statistical tests indicates that there is association between the newborn's weight and the type of pregnancy (Singleton or multiple), mother's age, gravidity and maternal disease.(P<0.0001). No relationship was found between the newborn's sex and his or her weight at birth.